SANCTIONS FOR PAWN PERPETRATORS OF EMBEZZLEMENT FROM THE PERSPECTIVE OF ISLAMIC CRIMINAL LAW - Nabil Al-Farid; Ramadani (Warmadewa Press, 2024)
Recently, there have often been criminal acts of possession or crimes against property which have attracted the attention of many people in Indonesia, especially the crime of criminal possession of motor vehicles. As defined in the Dutch language, healing is an act in the form of buying, receiving a pawn, pledging, receiving as a gift, hiding, storing, carrying, transporting, offering goods that are or are suspected of originating from a crime. The type of research in this study uses normative legal research, with a qualitative approach and the data sources used are primary data sources and secondary data sources with data collection techniques in the form of library studies. From the research conducted by the author, it can be concluded that it can be concluded based on the verses of the Qur'an and the hadith of the Prophet Muhammad above, that Islam allows pawning (rahn) provided that it is not used in a crime. In this case, the case previously described has been included in the category of crimes prohibited by Islam. So there is binding Islamic law along with sanctions that can be given to suspects. The crime of theft and detention is behavior that violates Islamic law which can be categorized as jarimah ta'zir. The aim of implementing the law for suspects is to obtain happiness in this world and the hereafter. Based on the opinion of Fiqh experts, it is stated that the punishment for people who commit crimes whose punishment is not regulated in the Al-Qur'an and Sunnah is ta'zir punishment. There are three forms of ta'zir punishment, namely: (1) punishment relating to the body, (2) punishment relating to a person's freedom, (3) punishment relating to property.